The effects of customer satisfaction service quality and perceived value on behavioural intentions in retail industry - Veloso, Cláudia M. (2020)
The retail industry has in the last decades assumed a preponderant role in the Portuguese economy, similar to that of other European countries, and is definitely one of the biggest and more vibrant industries nowadays. The significance of the retail industry for the Portuguese economy, a central sector for its growth and dynamic, and the relationship between service quality and efficiency of business are the motivations for this study. In a highly competitive industry, as is the retailing sector, it is crucial that organizations have a good knowledge of the business aspects that are important to their customers. The purpose of this study is to identify the dimensions of service quality and to evaluate the interrelationships among customer satisfaction, perceived value and behavioural intentions and service quality in the modern retail industry. A multi-level and hierarchical model is used as an instrument to synthesize the effects of customer satisfaction, service quality and perceived value on behavioural intentions of customers at retail stores. The results shown that, service perceived quality significantly influences customer satisfaction. Also perceived value and quality service are the main determinants of customer satisfaction. Additionally, customer satisfaction, retail service quality and perceived value significantly affect behavioural intentions towards the act of buying.